Pluralidade e qualidade no Jornal Nacional : Índice de Pluralidade Jornalística (IPJ) da cobertura sobre a reforma da previdência no governo Temer - Rodrigues, Érika Letícia de Oliveira (2019)
The research develops an experimental evaluation of the quality of the coverage of Jornal Nacional (JN) on the pension reform proposal (PEC 287/2016) presented by the Temer government, based on the Plurality requirement. The analysis, which aimed to identify the expression of conflicts of view and thus determine the Journalistic Plurality Index (IPJ), was performed in three steps: assembling the problem matrix, content analysis and calculating the IPJ. The evaluation considered the time span between the Federal Government's proposal to amend the Constitution in December 2016 and its suspension - in February 2018 - which resulted in an empirical corpus of 54 reports on the thematic axis investigated. At the end of the analysis it was possible to calculate the Journalistic Plurality Index (IPJ) of the main subthemes related to the proposed changes in Social Security, as well as to determine the IPJ of all pension reform coverage; and realize through these indices that the coverage of the National Journal on the subject remained partial for most of the period studied. In addition to the quality assessment, there was also the perspective of contributing to the experimental development of a research methodology, which is currently configured in a journalistic quality management software for editorial quality - Qualijor.